MEDIA PEMBELAJARAN TRAINER PENGUKURAN TATA CAHAYA PORTABLE PADA MATA KULIAH INSTALASI PENERANGAN LISTRIK DI PROGRAM STUDI S1 PENDIDIKAN TEKNIK ELEKTRO UNDIKSHA - Made Adi Krisman; I Putu Suka Arsa; I Gede Ratnaya (Jurnal Pendidikan Teknik Elektro Undiksha, 2021)
This study aims to create a Lightning Measurement Trainer, determine the feasibility and determine the student's response to the Portable Light Measurement Trainer learning media in the Electrical Lighting Installation course in the Electrical Engineering Education Study Program, Undiksha. This study uses a Research and Development (R&D) research and development method. Data collection in this study was carried out using a questionnaire method which was assessed by content experts, media experts and students. The results obtained: the results of the validation test from media experts get a percentage of 93% with proper qualifications, the results of the material/content expert test get a percentage of 95% with very decent qualifications, the results of the small group trial the lowest value of the response was 42 with the category/classificationn very good and the results of the large group test or field test the lowest value of the response was 39 with the cacategory/classification very good. Based on the research results, the portable Light Measurement Trainer learning media is feasible to use and gets a good response from students in the learning process in the Electrical Lighting Installation course in the Electrical Engineering Education Study Program, Undiksha.